2002
DOI: 10.1094/cchem.2002.79.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Sonicated Mung Bean, Potato, and Rice Starches

Abstract: Cereal Chem. 79(5):631-633Mung bean, potato, and rice starch solutions (5%, w/w) were sonicated for up to 5 min after heating, and their physicochemical properties were investigated. Alkaline viscosities, including the apparent and inherent viscosities of starches, decreased. The residues of the swollen starch granules after pasting and centrifugation were also reduced prominently by sonication. Average degree of polymerization did not change with sonication. The starch paste became more transparent, and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 6 publications
4
29
1
Order By: Relevance
“…In a study of the effect of sonication on mung bean, potato and rice starches, the degree of polymerisation did not change, but the starch paste became more transparent with a marked decrease in the hot paste viscosity at 70°C. This change was attributed to the sonication disrupting the swollen granules rather than breaking bonds within the starch molecule (Chung, Moon, Kim & Chun, 2002). These authors acknowledged that their results contrast with those of others who observed depolymerisation of starch and they attributed the lack of an effect of sonication on depolymerisation in their study to differences in the concentrations of starch used.…”
Section: Introductionmentioning
confidence: 70%
“…In a study of the effect of sonication on mung bean, potato and rice starches, the degree of polymerisation did not change, but the starch paste became more transparent with a marked decrease in the hot paste viscosity at 70°C. This change was attributed to the sonication disrupting the swollen granules rather than breaking bonds within the starch molecule (Chung, Moon, Kim & Chun, 2002). These authors acknowledged that their results contrast with those of others who observed depolymerisation of starch and they attributed the lack of an effect of sonication on depolymerisation in their study to differences in the concentrations of starch used.…”
Section: Introductionmentioning
confidence: 70%
“…Granule disintegration was determined using a method to measure the swelling power of starch (Chung et al, 2002). Five grams of sample was mixed with 500 mL of water in a beaker.…”
Section: Methodsmentioning
confidence: 99%
“…Sonically enhanced drying can be carried out at lower temperature than conventional methodology, which reduces the probability of oxidation or degradation of the food (Gallego-Juarez, 1998). Ultrasonic depolymerization has been applied on a variety of homo-and heteropolysaccharides such as dextran (Lorimer, Mason, Cuthbert and Brookfield, 1995), pullulan (Koda, Mori, Matsumoto and Nomura, 1994), chitosan (Chen, Chang, and Shyur, 1997), hyaluronic acid (Miyazaki, Yamamoto and Okada, 2001), xyloglucan (Vodeničarová, Dřimalová, Hromádková, Malovíková, and Ebringerová, 2006) and starch (Chung, Moon, Kim and Chun, 2002;Azhar and Hamdy, 1979). Starch is a main source of carbohydrate in the human diet.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al (2002) concluded that, under their conditions of paste preparation (in an RVA) and ultrasonication, the loss of paste viscosity was a result of disruption of swollen granules, rather than depolymerization of starch macromolecules. Jackson et al (1988Jackson et al ( , 1989 found that disruption of swollen granules in starch pastes leading to increased solubility of the polymer molecules, when done under proper conditions of ultrasound power, frequency, and treatment time, could be done without depolymerization (for chromatographic purposes).…”
Section: Effects On Starch Pastesmentioning
confidence: 99%